Winter motion mediates dynamic response of the Greenland Ice Sheet to warmer summers. Issue 15 (6th August 2013) - Sole, Andrew; Nienow, Peter; Bartholomew, Ian; Mair, Douglas; Cowton, Thomas; Tedstone, Andrew; King, Matt A.
Abstract: [1] We present ice velocities from a land‐terminating transect extending >115 km into the western Greenland Ice Sheet during three contrasting melt years (2009–2011) to determine whether enhanced melting accelerates dynamic mass loss. We find no significant correlation between surface melt and annual ice flow. There is however a positive correlation between melt and summer ice displacement, but a negative correlation with winter displacement. This response is consistent with hydro‐dynamic coupling; enhanced summer ice flow results from longer periods of increasing surface melting and greater duration ice surface to bed connections, while reduced winter motion is explicable by drainage of high basal water pressure regions by larger more extensive subglacial channels. Despite mean interannual surface melt variability of up to 70%, mean annual ice velocities changed by <7.5%. Increased summer melting thereby preconditions the ice‐bed interface for reduced winter motion resulting in limited dynamic sensitivity to interannual variations in surface melting. Key Points: Increased surface melting leads to faster ice flow in summer But increased melting also leads to slower ice flow in the subsequent winter The net effect of melting on interannual ice flow variation is therefore limited